Is Boccia XR an enjoyable and effective rehabilitation exercise for older adults? - Masataka Kataoka; Kyoji Sugiyama; Akira Iwata; Yumi Higuchi; Ryosuke Saga; Shinji Takahashi; Mitsuhiko Ikebuchi; Hiroaki Nakamura (PLoS ONE, 2025)
Background and objectives Maintaining activities of daily living (ADL) in older adults requires muscle strength and physical activity. However, exercise motivation often declines with age. Enjoyable activities can enhance motivation and effectiveness. Boccia is a recreational sport with rehabilitation potential but requires substantial space. This study evaluated the enjoyment and lower limb muscle activity of “Boccia XR,” a virtual adaptation designed for limited spaces, comparing it with traditional Boccia and treadmill walking. Methods Eighteen healthy older adults (mean age 73.3 ±  5.4 years) participated. Each performed Boccia XR, traditional Boccia, and treadmill walking in random order. Mood changes were assessed using the Profile of Mood States 2nd Edition (POMS2), and lower-limb muscle activity was measured via electromyography (EMG). Results Both Boccia XR and traditional Boccia significantly improved positive mood (Vigor-Activity) and reduced negative mood (Total Mood Disturbance) as compared to treadmill walking. Muscle activity analysis revealed that Boccia XR and traditional Boccia imposed muscle loads comparable to treadmill walking. Rectus femoris activity exceeded that of treadmill walking, and medial gastrocnemius activation was sufficient for strengthening in sedentary older adults during Boccia tasks. Conclusion Boccia XR is an enjoyable and effective physical activity for older adults, requiring less space, than traditional Boccia while providing physical benefits similar to treadmill walking. It may enhance exercise adherence and overall function in space-limited settings.